Implications of Covid-19 Pandemic on Drug Use and Substance Use Disorders in Sexual Minority Youth Worldwide: A Qualitative Review of the Literature and Future Research Agenda - Milshteyn, Yulya (Eximia, 2022)
Background. Substantial concern exists regarding the impact of the COVID-19 pandemic on substance use behaviours (SUD). Sexual minority youth are a particularly vulnerable group and more prone to display an array of mental health disparities and in particularly substance use disorders, than their heterosexual peers or even older people belonging to LGBT community. Aims. The purpose of the present meta-review is to examine the existing literature on the consequences of Covid-19 on drug use behaviors substance use disorders among sexual minority youth world-wide. Methods. An extensive search was conducted for all available research using the Google Scholar search engine as the primary source of data extraction. All relevant quantitative, qualitative and meta-analytical studies, dating back from 2019 - 2022 were included, all published in the English language. Results. Seven most pertinent studies were identified. All, but one employed quantitative, cross-sectional, longitudinal, population and survey-based research methods. Five studies were conducted in USA and two in Canada. Conclusion. Albeit a seemingly accumulative body of research on increased use of illicit drugs and substance use disorders among sexual minority young adults, it is undoubtedly clear that further qualitative, quantitative and mixed method studies are warranted in Israel and worldwide to shed light on the impact of Covid-19 on drug related trajectories and SUD in sexual minority youth. There is a need for implementation of specific tailored health care programs for this population.